A Coin-Like Peripheral Small Cell Lung Carcinoma Associated with Acute Paraneoplastic Axonal Guillain-Barre-Like Syndrome. Issue 22 (June 2015) - Jung, Ioan; Gurzu, Simona; Balasa, Rodica; Motataianu, Anca; Contac, Anca Otilia; Halmaciu, Ioana; Popescu, Septimiu; Simu, Iunius
Abstract : Abstract: A 65-year-old previously healthy male heavy smoker was hospitalized with a 2-week history of progressive muscle weakness in the lower and upper extremities. After 10 days of hospitalization, urinary sphincter incompetence and fecal incontinence were added and tetraparesis was established. The computer-tomography scan examination revealed a massive right hydrothorax and multifocal solid acinar structures with peripheral localization in the left lung, which suggested pulmonary cancer. Bone marrow metastases were also suspected. Based on the examination results, the final diagnosis was acute paraneoplastic axonal Guillain-Barre-like syndrome. The patient died 3 weeks after hospitalization. At autopsy, bronchopneumonia and a right hydrothorax were confirmed. Several 4 to 5-mm-sized round peripherally located white nodules were identified in the left lung, without any central tumor mass. Under microscope, a coin-shaped peripheral/subpleural small cell carcinoma was diagnosed, with generalized bone metastases. A huge thrombus in the abdominal aorta and acute pancreatitis was also seen at autopsy. This case highlights the difficulty of diagnosis of lung carcinomas and the necessity of a complex differential diagnosis of severe progressive ascending neuropathies. This is the 6th reported case of small cell lung cancer-associated acute Guillain-Barre-like syndrome and the first report about an association with a coin-like peripheral pattern.